Analisis Total Productive Maintenance pada Mesin Reaktor Pompa Slurry 22P303A untuk Mengurangi Six Big Losses dengan Maintenance Value Stream Mapping Produksi II B PT PG - Pangesti, Arwinda; Nugraha, Isna (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
The manufacturing industry currently faces major challenges in maintaining and improving the operational performance of production machines to ensure efficiency and product quality. PT PG is engaged in the manufacturing industry, which seeks to increase the effectiveness and efficiency of production II B, especially by using a slurry pump machine during January to June. This study aims to determine the Total Productive Maintenance and how to improve during downtime and find out how to reduce the Six Big Losses with improvements using MVSM. The method used is TPM by reducing the Six Big Losses and using the maintenance value stream mapping (MVSM) approach. The results show that the Total Productive Maintenance (TPM) on the 22P303A reactor slurry pump machine at PT PG, especially in Production Unit II, namely in January of 67.06%, February of 50.32%, March of 58.42%, April of 59.71%, in May of 32%, and in June of 53.40%. And from the Six Big Losses Analysis research shows that downtime is the biggest loss with a total of 329 minutes or representing 35% of the total operational time. The biggest loss comes from Idling and Minor Stopage Losses with a total repair time using MVSM of 171 minutes.. Keywords: Maintenance Value Stream Mapping (MVSM),Slurry Pump Machine, Total Productive Maintenance